The significance of therapeutic waters of Swoszowice, Krzeszowice and Mateczny in the development of spa tourism // Znaczenie wód leczniczych Swoszowic, Krzeszowic i Matecznego dla rozwoju turystyki uzdrowiskowej - Jamorska, Izabela (Geotourism/Geoturystyka, 2018)
Mineral waters have been applied for therapeutic purposes in Cracow since the fifteenth century. The complex geological structure of this area has had considerable influence upon various hydrogeological conditions. Sulphide waters in Cracow and in its vicinity are connected to the presence of gypsiferous formations occurring within the Miocene rocks deposits. Sulphide mineral waters help to treat such cases as: osteoarthritis, diseases of digestive system and nervous system, foodborne diseases, skin diseases, and illnesses of movument organs. The springs of those waters are located in a region that is particularly attractive to tourists. Both historical and natural attractions of Cracow and its neighbouring area create a big opportunity for further development of spa tourism there. This fashionable form of recreation may help old forgotten sulphide waters and Cracow health resorts revive their glamour. // Wody mineralne znane były i stosowane w Krakowie w celach leczniczych od XVw. Skomplikowana budowa geologiczna tego obszaru wpływa na różnorodne warunki hydrogeologiczne. Wody siarczkowe Krakowa i okolic związane są z obecnością na tym obszarze utworów gipsonośnych występujących w obrębie piętra mioceńskiego. Siarczkowe wody lecznicze pomagają w leczeniu takich dolegliwości jak: choroby zwyrodnieniowe stawów, schorzeń skóry, przewodu pokarmowego, systemu nerwowego, zatruć pokarmowych i pourazowych narządu ruchu. Źródła tych wód znajdują się w atrakcyjnym turystycznie regionie Polski. Zarówno historyczne, jak i przyrodnicze atrakcje Krakowa i okolic stwarzają ogromne możliwości rozwoju na tym obszarze turystyki uzdrowiskowej. Ta modna w obecnych czasach forma wypoczynku może pomóc zapomnianym wodom siarczkowym i uzdrowiskom krakowskim przywrócić ich dawną świetlność.